PENGARUH KUALITAS PRODUK DAN LAYANAN TERHADAP KEPUASAN PELANGGAN SERTA DAMPAKNYA PADA LOYALITAS PELANGGAN DI RESTORAN PIZZA HUT CABANG JATIWARINGIN - Wahyu Murti; Wirda Nursanti; Suliati (Jurnal Manajemen FE-UB, 2023)
This study aims to examine and analyze the effect of product and service quality on customer satisfaction and its impact on customer loyalty. The data used in this study are primary data taken from the results of questionnaire responses by pizza hut customers at the Jatiwaringin branch, East Jakarta. The data processing method uses the path analysis method with the help of the SPSS version 21 analysis tool. The statistical test in this study uses the goodness of fit test. The results showed that product quality had a direct and significant positive effect directly or indirectly through customer satisfaction on customer loyalty, service had a positive and significant effect directly and indirectly through customer satisfaction on customer loyalty and customer satisfaction had a direct positive effect on customer loyalty.   Keywords: product quality, service, customer satisfaction, customer loyalty.